1969
DOI: 10.1126/science.164.3885.1285
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinant of a Ribosomal Protein: K Locus

Abstract: One of the ribosomal proteins (30S-8B) of Escherichia coli B has a greater electrophoretic mobility than the homologous protein (30S-8K) in E. coli K. The amino acid compositions, tryptic peptides, and cyanogen bromide peptides of these two homologous proteins unambiguously indicate that the genetic locus which determines the electrophoretic mobility of protein 30S-8 is the structural gene for this protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
1976
1976

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Leboy,Cox,and Flaks (162) found that a 30S ribosomal protein (P5) from E. coli strain K-12 is different from the corresponding protein from other E. coil strains in its electrophoretic mobility on polyacrylamide gels. The difference between these two proteins was confirmed by chemical analysis (18,317). This character (K character) can be transferred from K-12 strains into B strains by PI transduction by using streptomycin as a selective marker; hence, the genetic determinant, the K locus, is very closely linked to the str locus (162,188).…”
Section: Genetics Of Ribosomesmentioning
confidence: 82%
“…Leboy,Cox,and Flaks (162) found that a 30S ribosomal protein (P5) from E. coli strain K-12 is different from the corresponding protein from other E. coil strains in its electrophoretic mobility on polyacrylamide gels. The difference between these two proteins was confirmed by chemical analysis (18,317). This character (K character) can be transferred from K-12 strains into B strains by PI transduction by using streptomycin as a selective marker; hence, the genetic determinant, the K locus, is very closely linked to the str locus (162,188).…”
Section: Genetics Of Ribosomesmentioning
confidence: 82%